Die kartographische Synopsis als Instrument der natur- und sozialgeographischen Theoriebildung - Dürr, Heiner (ERDKUNDE, 1973)
The cartographic synopsis, i.e. the juxtaposition of idential-scale maps with physical and social geography content, is investigated with reference to its contribution to theory construction in geography. Using a sample area of 58 sq km in the northern part of the Lüneburg Heath, three variations of this method are tested and each related to one particular aspect of geographical theory: the map of historical processes is related to the theory of natural regions (part I), the map of historic structure is linked to efforts to explain field patterns and ownership forms (II), and the map of contemporary processes is related to the theory of agricultural land use (III). The main methodological result which emerges is that, in all three cases, cartographic synopsis from large-scale maps only allows the construction of crude working hypotheses and is therefore only usable in the initial stages of theory building. The synopses used in the examples yield the following working hypotheses: Part I: the patterns of soil forms on sandy and loamy substrata is strongly influenced by the history of land use at those locations and can thus be said to have been moulded by human factors. Part II: the identification of traditional field patterns and ownership forms (clustered narrow-strip ownership and ownership of commons) can be linked to a relict perception of natural factors in the affected fields. Part III: analysis of changes in agricultural land use between 1938 and 1968 yields empirical support for Hartke’s theoretical propositions concerning group-specificity in the evaluation of natural factors and for their influence on decisions to change agricultural land use. In these hypotheses, implications are seen for future research strategies in these subdisciplines of geography.